(Co, Ni)Sn0.5 Nanoparticles Supported on Hierarchical Carbon Nitride‐Graphene‐Based Electrocatalysts for the Oxygen Reduction Reaction. Issue 14 (27th June 2018) - Negro, Enrico; Nale, Angeloclaudio; Vezzù, Keti; Pagot, Gioele; Herve Bang, Yannick; Polizzi, Stefano; Colombo, Massimo; Prato, Mirko; Crociani, Laura; Bonaccorso, Francesco; Di Noto, Vito
Abstract: The synthesis of new " Pt‐free " electrocatalysts (ECs) for the oxygen reduction reaction (ORR) is reported. The ECs are characterized by a hierarchical " core‐shell " morphology; the " core " is made of graphene, that is covered by a cratered, microporous carbon nitride (CN) " shell ". The latter supports nanoparticles of M1 and Sn metals (M1=Co; Ni) in " coordination nests ". The latter are holes in the CN matrix, whose walls consist of N‐ and C‐ligands. Two groups of ECs are studied: (i) " pristine " ECs; and (ii) " activated " ECs, that are obtained from the " pristine " ECs by means of a suitable activation process (A ) aimed at improving the performance in the ORR. Here, the interplay existent between (i) the chemical composition, morphology, structure and A; and (ii) the ORR performance and mechanism is investigated. The resulting insights improve the fundamental understanding of this family of ECs and open the door to the devising of new preparations of " Pt‐free " ECs for the ORR, which: (i) are stabilized by a CN matrix and; (ii) exhibit an improved performance. Abstract : Thrilled to the core : new " Pt‐free " " core‐shell " electrocatalysts (ECs) for the oxygen reduction reaction (ORR) are devised. A graphene " core " is covered by a carbon nitride " shell " matrix embedding active sites based on Sn and either Co or Ni. The interplay between the chemical composition, morphology, structure and the ORR performance and mechanism is elucidated.